Help Starts Here / The Maladjusted Child in the Ordinary School - Garside Roger Forbes; Kolvin Israel; Macmillan Angus; Nicol Arthur Rory (Tavistock Publications, 1981)
Foreword, Preface and Acknowledgements, Introduction, Getting Introduction: Basic Concepts, Some Basic Problems in Evaluation, Method and Background, Aims and Method, The Children and Their Schools and Families and Therapists, Treatment Approaches, Behaviour Modification Approach, The Nurturing Approach - A Teacher-Aide Programme, Parent Counselling-Teacher Consultation, Group Therapy for Children, Results and Conclusions, Final Analysis: Junior and Senior Schools, Summary and Conclusions, Technical Appendices, Evaluative Measures Used, Methods, Results, School and Therapist Effects on Outcome, References, Name and Subject Index.